ANALYSIS OF TOKOPEDIA’S ADVERTISING CREATIVITY “WAKTU INDONESIA BELANJA” - Jamiati KN; Naila Waliya Hamima; Velda Ardia (The Indonesian Journal of Communication Studies, 2020)
Companies must have innovative ways of communicating messages to compete with other companies because of the many new companies that have sprung up. One of them is by using television media. However, with the increasing number of companies placing advertisements, the number of TV stations in Indonesia is now around 1027 television stations. The public's tendency to switch channels has made advertising conditions worse so that creative advertising is needed. Using a qualitative descriptive method focuses on describing, analyzing, and interpreting Tokopedia advertisements from television media. The data collection techniques used were observation, literature study, and documentation. The results showed that the Tokopedia WIB "Waktu Indonesia Belanja" advertisement was always on television. The advert is inspiring and easy to remember. This advertising has creativity as seen from the indicators of connectedness, suitability, and novelty.